The room-product-effect and its application to investigate the desirability of designed products: a review - Wang, Zheng; R. A. A. Effendi, Raja Ahmad; Whitfield, T. W. Allan; Barron, Deirdre; Ni, Wei (Springer, 2024)
The Room-Effect originated in environmental psychology, where the room a person was in influences how they were judged by people. Subsequent studies extended this to the Room-Product-Effect indicating its application beyond the original domain of rooms or environments to designed products. It provides a new research method for investigating the effect a product has on the person associated with it. However, no review exists summarizing the research into the Room-Product-Effect from its inception to the present. Therefore, this paper provides a systematic review that elucidates the origin, and evolution of the Room-Product-Effect, while also describing the research methods employed in its investigation. To accomplish this, six databases (Scopus, Web of Science, ScienceDirect, JStor, ProQuest, China National Knowledge Infrastructure) were used to search and locate relevant studies (the search was conducted from the time of database construction to 1 June 2023). A total of 7080 articles were retrieved. Eighteen articles that met the inclusion criteria were identified and included. This review introduces the concept, its origins, the development of the Room-Effect and the subsequent Room-Product-Effect. Additionally, ongoing research into the Room-Product-Effect are identified.